Net Benefit of Anticoagulation in Subclinical Device-Detected Atrial Fibrillation - Winsten, Aleksi K.; Langen, Ville; Airaksinen, K. E. Juhani; Teppo, Konsta (American Medical Association (AMA), 2025)
Importance The role of anticoagulation for stroke prevention in patients with device-detected atrial high-rate episodes, also known as subclinical atrial fibrillation (AF), is a subject of equipoise.
Objective To assess the net benefit of nonvitamin K antagonist oral anticoagulants (NOACs) in patients with device-detected subclinical AF.
Design, Setting, and Participants Decision analytical model run with 10 000 patients with anticoagulation and 10 000 patients without anticoagulation in a clinical scenario of deciding whether to start NOACs for stroke prevention in patients with subclinical AF. A Markov decision model was conducted on October 1, 2024, to estimate net outcomes of NOACs. The patients had stroke risk and bleeding risks similar to those of patients in randomized trials of anticoagulation in subclinical AF.
Exposure Anticoagulation was modeled to decrease the risk of ischemic stroke by 32% and increase the risk of major bleeding by 62%. In probabilistic sensitivity analyses, the 95% CIs for treatment effect sizes were also considered.
Main Outcomes and Measures The main outcome measure for overall net benefit was the cumulative quality-adjusted life-years (QALYs) during the simulation. The model considered the number and severity of ischemic strokes, hemorrhagic strokes, other intracranial bleeds, and extracranial bleeds, as well as the number of deaths during a 10-year simulation.
Results When comparing the 2 cohorts of 10 000 patients (mean age, 77 years; 3700 [37%] women), those receiving NOAC therapy had 233 fewer ischemic strokes (21.7%), 55 fewer deaths (1.1%), and 453 more major bleeding events (37.3%) over a 10-year simulation period. Per patient, these differences translated to approximately 1 additional quality-adjusted week of life (0.024 QALYs) with NOAC treatment during the 10-year simulation. When the 95% CIs of treatment effect sizes were considered in probabilistic sensitivity analysis, there was a 65.8% probability that NOAC treatment leads to more QALYs than withholding treatment.
Conclusions and Relevance In this analytical model study, initiating NOACs in patients with device-detected subclinical AF was associated with a minimal increase in QALYs. However, the benefits were uncertain, and the effect size of the overall net benefit does not appear to be clinically meaningful.